The Impact of Online Learning Activities on Junior Highschool Students in English Subjects and Islamic Views on Education - Adjie Rangga Yasa; Dyah Kusumastuti (Universitas Muhammadiyah Purwokerto, 2022)
Even when the situation makes students unable to meet with teachers directly, the learning process has to keep going so that there is no intelligence gap for students who are still in school during the covid-19 pandemic. The method used in this study is an interview using five questions as the research instrument and has 6 research subjects, consist of 1 English teacher and 5 junior high school students. This research was held to describe the actual conditions at the junior high school level, especially the use of technology and also online learning within the scope of English language education then relate it to the Islamic view of science. Interestingly, the researcher emphasized the results which stated that students and teachers were not quite satisfied with online learning that had been going on for more than a year both in terms of process and results.